2009
DOI: 10.1590/s0044-59672009000300017
|View full text |Cite
|
Sign up to set email alerts
|

Omnivory and resource - sharing in nutrient - deficient Rio Negro waters: stabilization of biodiversity?

Abstract: Amazonian biodiversity is notorious, this is also valid for the fauna of the mineral-deficient waters of the Rio Negro System. Some 25 years of research on the benthic fauna of Central Amazonian streams resulted in species-rich foodwebs with a high degree of omnivory within dense animal communities. To exemplify the taxonomic range of omnivorous consumers, the detailed resource spectra of 18 consumer species, including Protozoa (2 species), Platyhelminthes (1 species), insects (2 species), fish (6 species) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
9
0
2
Order By: Relevance
“…Many authors have shown that Palaemonidae species also have a diet made up of a number of different items, although detritus is usually an important and quite common component (Howard 1984, Collins & Paggi 1998, Albertoni et al 2003, Walker 2009). Not only does this group, but also those members of the Peneidae family present in estuarial environments, use the detritus (Masitah & Chong 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many authors have shown that Palaemonidae species also have a diet made up of a number of different items, although detritus is usually an important and quite common component (Howard 1984, Collins & Paggi 1998, Albertoni et al 2003, Walker 2009). Not only does this group, but also those members of the Peneidae family present in estuarial environments, use the detritus (Masitah & Chong 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In the theoretical concepts, omnivores in aquatic continental systems help stabilize populations and communities by combining the resources with different conversion efficiencies (Krivan & Diehl 2005, Walker 2009). This characteristic regulates the flow of energy and the recycling of nutrients (Evans-White et al 2001, Buck et al 2003, Williner 2010.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…was its most important prey followed by copepods (Cyclopoda) and Cladocera. Although vegetal tissues and detritus were found in the diet of this genus, probably these items were in the stomach of digested prey organisms as suggested by Walker (2009). However, some copepods and cladocerans can inhabit benthos and littoral plankton and their presence in the diet of Sympetrum sp.…”
Section: Discussionmentioning
confidence: 76%